Pemberdayaan Kelompok Wanita Tani dalam Optimalisasi Produksi dan Pemasaran Digital Sayuran Organik Mewujudkan Swasembada Pangan di Kelurahan Karangmalang, Kota Semarang - Nur Muttaqien Zuhri; Ida Kristiana; Ari Dwi Astono; Nanda Wanifa Lutfiani; Siti Ma`Rufah; Adistine Zafir Yunianur; Peby Widyaningsih; Sayid Labib Mustofa; Hedy Ilham Widyatama (BADAN PENERBIT STIEPARI PRESS, 2026)
This community service program was implemented to empower the Srikandi Women Farmers Group (KWT) in Karangmalang Village, Mijen District, Semarang City, by increasing their capacity to produce and market organic vegetables. This activity aims to strengthen the technical capabilities of group members in organic hydroponic cultivation and expand market access through the application of digital marketing. The implementation methods include preparation, training and practice in Nutrient Film Technique (NFT) hydroponic cultivation, social media-based digital marketing training, as well as evaluation and ongoing assistance. The results of the activity showed a 70.6% increase in participants' competence, with the main indicators of success being the ability to assemble hydroponic installations, manage production independently, and market products digitally under the “Srikandi Fresh” brand. In addition to increasing productivity and economic value, this activity also fostered new awareness of sustainable agriculture, strengthened group solidarity, and gave rise to local leadership that is adaptive to modern agricultural technology. This activity has positive implications for strengthening the role of women in local food security based on organic agriculture and the digital economy.